Effectiveness of Mindfulness-Based Therapy on Emotion Regulation and Perception of Rejection in Women with Multiple Sclerosis - Najafi Aliehkolaei, Mohammad; Ghalandari, Elham; Mostafavi, Elham (Health Nexus, 2023)
This study aimed to investigate the effectiveness of mindfulness-based therapy on emotion regulation and perception of rejection among women with multiple sclerosis using a quasi-experimental pretest-posttest and follow-up design with a control group. The population of this study included all women with multiple sclerosis in Tehran in the year 2023, who were registered with the Multiple Sclerosis Society of Iran. Using convenience sampling, 30 participants were selected and randomly assigned to two groups of 15, experimental and control. The experimental group received mindfulness-based therapy in eight 90-minute sessions (two sessions per week), while the control group received no intervention. The research instruments included the Emotion Regulation Questionnaire (ERQ) by Gross and John (2003) and the Perception of Rejection Questionnaire (PEQ) by Rohner et al. (1978). The results showed that after adjusting for pretest scores, there was a significant effect in the between-group variables for emotion regulation (F = 4.49, p = 0.001) and perception of rejection (F = 47.34, p = 0.001). Therefore, it can be concluded that mindfulness-based therapy impacts emotion regulation and perception of rejection variables, and these differences were maintained at the follow-up stage. The results indicate that mindfulness-based therapy is effective for emotion regulation and perception of rejection and can be utilized alongside medical treatments for women with multiple sclerosis.